Prostate cancer early detection - Kawachi, M; Bahnson, R; Barry, M; Carroll, P; Carter, H; Catalona, W; Epstein, J; Etzioni, R; Hemstreet, G; Howe, R; Kopin, J; Lange, P; et al. (2007)
Since the early 1990s when the ACS developed guidelines for the early detection of prostate cancer, many variants of the tPSA assay have been introduced to increase the sensitivity of screening programs (cancer detection) while maintaining specificity (elimination of unnecessary biopsies). Again, the NCCN guidelines recommend how individuals and their physicians can use these new methods rationally for the early detection of prostate cancer. These guidelines are not designed to provide an argument for using early detection programs for prostate cancer, but are meant to provide a vehicle with which early detection efforts can be practiced in an evidence-based, systematic fashion in patients who choose to participate in these programs.56 These NCCN guidelines incorporate many new validated findings in addition to the DRE and tPSA test. These new factors include percent fPSA, PSAV, cPSA, biopsy pathology, and TRUS-guided biopsy techniques. The panel will re-examine the clinical usefulness of these new modalities annually, and the guidelines will be modified accordingly. In addition, future iterations of these guidelines may incorporate new serum markers currently undergoing clinical investigation. The goal of the NCCN and this guideline panel in updating these algorithms is to help men and clinicians choose a program of early detection of prostate cancer and make decisions about the need for prostate biopsy. Any clinician who uses these guidelines is expected to exercise independent medical judgment in the context of the individual clinical circumstances to determine each patient's need for prostate biopsy. These guidelines will continue to evolve as the field of prostate cancer advances. © Journal of the National Comprehensive Cancer Network.